Volcanism‐induced sedimentation and model: A case study of the Upper Jurassic‐Lower Cretaceous sediments in the Liuhe‐Tonghua Basin, NE China. (31st July 2020) - Zhou, Yang; Cheng, Rihui; Shen, Yanjie; Xu, Zhongjie; Song, Libin; Liu, Guodong
Abstract : Understanding how the lacustrine environment adapts to volcanism and the relevant products is one of the key goals of volcaniclastic sedimentology. Mixed sediments can be deposited in lacustrine basins during the interaction between volcano and environment. This article is focus on the lithology, lithofacies, association, and sedimentary sequence of the Late Jurassic‐Early Cretaceous mixed sediments from the Liuhe‐Tonghua Basin, revealing the transportation‐accumulation processes of volcanic materials from subaerial eruption into water or subaqueous eruption mingling with terrigenous clasts. Four kinds of mixed‐sediment rocks are identified including tuffaceous sandstone, tuff‐lapilli tuff, breccia‐agglomerate/lava and tuff lava/lava, and six lithofacies associations are identified: (a) base surge and pyroclastic flow, interpreted as the middle‐distal end of a mixed‐fan delta; (b) base surge‐pyroclastic flow and turbidite flow, interpreted as the distal end of a mixed‐fan delta; (c) base surge‐pyroclastic flow‐turbidite flow and mud deposits, interpreted as a mixed subaqueous fan; (d) sand sheet of the base surge and mud deposits, interpreted as a deepwater region; (e) subaerial volcanic edifice, interpreted as a volcanic vent‐proximal slope; (f) subaqueous volcanic edifice, interpreted as a volcanic slope. These associations may exhibit different spatial occurrences and palaeogeographic distributions, representing the transition from a volcanic to a sedimentary environment in the source to sink system, and an ideal mixed sedimentation model is established based on these associations and relevant mud deposits. These associations also exhibit a typical volcanic‐sedimentary sequence including terrigenous lowstand sediments in extensional settings and mixed volcanic and terrigenous transgressive‐highstand sediments in trans‐extensional settings. This article presents a case of volcaniclastic sedimentation (mixed sedimentation) of Cretaceous volcano‐fault basin in Northeast China, which can provide a reference for the lacustrine volcaniclastic deposition in other similar genetic basins around the world. Abstract : This picture shows the characteristics of the palaeogeographic distributions of various lithofacies associations mentioned in this article about the volcanism‐induced sedimentation and the source to sink system from a volcanic environment to a sedimentary environment. Picture A is a plant view about the six lithofacies associations in this article. Picture B is a section about this mixed sedimentation model in a volcanic source to sink system.